Analysis of methyl DNA adducts and metabolites in BEAS-2B cells induced by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone. (2nd September 2019) - Wang, Huiting; Li, Xiang; Zhao, Ge; Xu, Liangtao; Wang, Sheng; Nie, Mingxuan; Hua, Chenfeng; Shang, Pingping; Pan, Lining; Zhao, Junwei; Qiao, Liangjun; Liu, Kejian; et al.
Abstract: The tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is classified as a Group 1 human carcinogen. It is metabolically activated by P450 enzymes to intermediate methylate and pyridyloxobutylate DNA, resulting in the formation of DNA adduct that is critical for the carcinogenicity of NNK. To directly and objectively examine the DNA adduct formation profiles without the complexity of factors in vivo, in the present study, five kinds of methyl DNA adducts were first identified in the incubation model of NNK established with human lung epithelial cells (BEAS-2B). The level of methyl DNA adducts and metabolites of NNK were quantitatively analyzed, respectively. With the increase of exposure time and dose, the level of methyl DNA adducts and metabolites increased. Furthermore, with the changes of the activity of P450 enzymes, which is the main enzyme regulating the α-hydroxylation of NNK, we found the levels of both methyl adducts and metabolites formed via α-hydroxylation in experimental groups showed the same trend compared with those in control group, while the metabolites formed via other pathways changed in the opposite trend. The result proves that the methyl adducts induced by NNK generate via α-hydroxylation pathway in BEAS-2B cells.